DETERMINAN PENGHINDARAN PAJAK: STUDI DARI PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Siti Meiditania; Maryati Maryati (Jurnal Proaksi, 2025)
Main Purpose - This study aims to determine the effect of profitability, sales growth, transfer pricing and capital intensity on tax avoidance in mining companies. Method - Using a quantitative approach, this research analyzes secondary data from 19 companies that were chosen through purposive sampling, yielding 95 observations. E-Views 12 software is used as the data analysis tool for panel data regression analysis. Main Findings - The phenomenon of tax ratio in Indonesia, which remains relatively low compared to the international average, indicates that tax revenue is still not optimal in supporting the national budget. According to data, Indonesia's tax ratio during the period of 2019–2023 ranged from an average of 10–12%, well below the standard average of 15–20% in developed countries. The results revealed that profitability, sales growth, and capital intensity affect tax avoidance, while transfer pricing has no effect on tax avoidance. Theory and Practical Implications - Future research should expand the scope by including additional variables, such as leverage and thin capitalization, and exploring other sectors to provide a broader understanding of tax avoidance practices. Novelty - This research adds a variable of sales growth, focus on the mining sector as the object of research, and the adoption of the Slippery Slope Theory to replace the previously used Agency Theory.